Po(d)stawy projektowe - Mrowczyk, Jacek (Instytut Sztuk Pięknych Uniwersytetu Rzeszowskiego, 2019)
The paper discusses the problem of changes in the job of a graphic designer, with a special focus on developing design attitudes. The latter are connected with the constantly redefined tasks set before designers. Mrowczyk’s interlocutors – Tomek Bierkowski from the Academy of Fine Arts in Katowice, and Marcel Benčik from Academy of Fine Arts and Design in Bratislava, are trying to establish e.g. what has shaped their design attitudes, how education influences successive generations and what may be the role of designers in building civil society. The article includes references to among others Victor Papanek, Jorge Frascara and Bruce Mau. The article is illustrated with the works of both experienced designers and Polish and foreign students.
Design Attitudes
Keywords: projektowanie; projektowanie graficzne; postawy projektowe; projektowanie prospołeczne; odpowiedzialność projektanta; design; graphic design; design attitudes; social design; designer responsibility